Penilaian Kepuasan Pengguna Aplikasi Absensi My W2u Di Pt. Wom Finance - Tuti Haryanti; Elisa Yuliana Wati; Laela Kurniawati (BETRIK, 2025)
Global influence is also felt in the fields of economics and management, which are closely related to technology, particularly with the emergence of advanced technological tools that make human tasks easier. One significant development in information technology is the increasing demand for attendance applications, which facilitate employees in recording their attendance anytime and anywhere. Human resources are a crucial asset in both large and small-scale organizations, as they drive, guide, sustain, and develop the organization in response to societal and era-related demands. One company that has innovated in digital human resource management is PT. Wom Finance, which introduced an attendance application to streamline employee attendance and employee data processing. Research method used in this study is descriptive with a quantitative approach. Data was collected using a questionnaire from 23 respondents. Conclusions drawn from the analysis show that: the Content variable (X1) results in a satisfaction score of 85.5%, Accuracy (X2) at 84.7%, Format (X3) at 83.4%, Ease of Use at 86.5%, and Timeliness at 86.9%. These percentages indicate that employees of PT Wom Finance, Headquarters, IT Development Division, are very satisfied with the My W2U application